Status Asthmaticus - J.S Partana (Paediatrica Indonesiana, 1975)
The therapy of status asthmaticus must be rational. Thus it is important to evaluate: 1. the severity and duration of an asthmatic attack. 2. the degree of dehydration. 3. whether infection plays a role. 4. all medication previously administered. 5. any possible complication.Treatment is as follows :Fluid and electrolyte therapy is important not only for the correction of dehydration and electrolyte disturbances but also for preventing inspissation of mucus in the bronchi. The best route of fluid administration is intravenous.Potassium iodide orally administered may be helpful as an expectorant.After hydration and normal acid-base balance have been established, epinephrine may be of benefit.Aminophylline is effective when administered intravenously. It should be used with extreme caution: the dose should not exceed 3 mg per kg of body weight, it should be given slowly and should not be given more frequently than every 8 hours.Corticosteroids should be administered, especially in cases who have received suppressive doses previously.Humidified oxygen administration is of the utmost importance.Antibiotics are recommended when infection is suspected.Management of complications.